Экономическая безопасность: региональный аспект - Зименкова, Е.Н.; Ячменева, В.М. (Культура народов Причерноморья, 2014)
Статья посвящена исследованию сущности экономической безопасности. Приводится
обзор научных взглядов на данную категорию, определяются виды экономической безопасности и
иерархия приоритетов. Дается авторское определение к понятию “регион”. Рассматривается три
уровня экономической безопасности: мезоуровень – экономическая безопасность регионов, как
административно-территориальных единиц государства; макроуровень – экономическая безопасность
государства; мега уровень – экономическая безопасность транснациональных и трансграничных
регионов. Стаття присвячена дослідженню сутності економічної безпеки. Наводиться огляд наукових
поглядів на дану категорію, визначаються види економічної безпеки та ієрархія пріоритетів. Дається
авторське визначення поняття "регіон". Розглядається три рівня економічної безпеки: мезорівень -
економічна безпека регіонів як адміністративно-територіальних одиниць держави; макрорівень -
економічна безпека держави; мега рівень - економічна безпека транснаціональних і транскордонних
регіонів. The article is devoted to the analysis of the essence of the concept of "economic security". Provides
an overview of the scientific views on this category, we examine the conceptual and categorical apparatus. The
author suggests his own definition of "region". The article gives a General idea about the economic security of
the region, determine the place and role of economic security in the region in the system of economic security of
the state, economic security and the hierarchy of priorities.
The relevance of the article there is no doubt, as the country's economic security is the basis of the state and
consists of a set of economic security of its regions, because the regions are the determining factor in the
formation of a stable economy. The area of economic security today is poorly studied due to the dynamic
external environment. Changes that are inherent in any system are the determining factor unresolved problems
of economic security at different levels.
Feature of the approach is the identification of distinctive features and prioritization of economic security of the
region at different levels: the meso - economic security of the regions as administrative-territorial units of the
state; macro - economic security of the state; mega level of economic security, transnational and transboundary
regions.